2019
DOI: 10.1177/1535370218824547
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 and IL-23/Th17 axis in systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a very complex disease where multiple immunological pathways can concur in inducing tissue damage. Cytokines are key mediators in this process and among them the role of interleukin (IL)-12 and the IL-23/Th17 axis has recently emerged. IL-12 and IL-23 have a heterodimeric structure with a common subunit, named p40. Although they share a partially common structure, their functions appear slightly different. Indeed, IL-12 is a key cytokine in inducing an efficient T helper 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 97 publications
7
43
0
3
Order By: Relevance
“…The role of IL17A in regulating granulopoiesis and neutrophil recruitment via induction of G-CSF is well recognized under homeostatic conditions 34,70 and a few studies have identified IL17-A as important for neutrophil recruitment to the sites of sterile inflammation 71,72 . In lupus, elevated IL-17A expression is found in cutaneous lesions 73,74 and increased circulating IL-17A levels have been associated with worse disease manifestations 75,76 , although the specific relationship to neutrophils, a pathogenic population in this disease, 11,[15][16][17] remains unexplored. Besides its direct effects on G-CSF-mediated mobilization of neutrophils from the bone marrow, IL-17A may also contribute to neutrophil homing to the kidney by stimulating expression of adhesion molecules (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The role of IL17A in regulating granulopoiesis and neutrophil recruitment via induction of G-CSF is well recognized under homeostatic conditions 34,70 and a few studies have identified IL17-A as important for neutrophil recruitment to the sites of sterile inflammation 71,72 . In lupus, elevated IL-17A expression is found in cutaneous lesions 73,74 and increased circulating IL-17A levels have been associated with worse disease manifestations 75,76 , although the specific relationship to neutrophils, a pathogenic population in this disease, 11,[15][16][17] remains unexplored. Besides its direct effects on G-CSF-mediated mobilization of neutrophils from the bone marrow, IL-17A may also contribute to neutrophil homing to the kidney by stimulating expression of adhesion molecules (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Вызывают интерес предварительные данные об эффективности БАРИ у пациентов с ювенильным дерматомиозитом [118], на фоне лечения которым отмечена положительная динамика большинства клинических показателей, входящих в стандарты оценки эффективности терапии (ACR/EULAR) этого заболевания, а также счета 28 IRG (interferon-regulated gene) и сывороточной концентрации IP-10 (Interferon gamma-induced protein 10) -хемокина, играющего важную роль в иммунопатогенезе ИВРЗ [119]. Следует обратить внимание и на другой потенциально важный механизм, определяющий эффективность БАРИ при СКВ и других ИВРЗ, связанный с ингибицией ИЛ12 и ИЛ23 (JAK2/TYK2-зависимые цитокины), которые вызывают патологическую активацию Тh1и Тh2-типов иммунного ответа и гиперпродукции аутоантител В-клетками [120]. В настоящее время проводится серия РКИ, касающихся изучения эффективности терапии БАРИ при СКВ (фаза II -NCT02708095, фаза III: NCN03843125, NCT03616964), гигантоклеточном артериите (фаза II -NCT03026504), ревматической полимиалгии (фаза II -NCT04027101).…”
Section: перспек тивыunclassified
“…Отмечена связь между развитием СКВ и полиморфизмом генов, участвующих в сигнализации JAK-STAT (JAK2, TYK2 и STAT4) [48], и гиперпродукцией широкого спектра JAK-STATзависимых цитокинов, в первую очередь ИФН типа I (ИФНα/β), ИФНγ, а также ИЛ2, ИЛ6, ИЛ21, ИЛ17, ИЛ12, ИЛ23 и др. [49,50]. Все это вместе взятое привлекло внимание к возможности использования ингибиторов JAK в лечении СКВ [50,51].…”
Section: другие иммуновоспалительные ревматические заболеванияunclassified